The role of emotional similarity and emotional accuracy in belonging and stress among first-generation and continuing-generation students - Lawrie, Smaranda Ioana; Kim, Heejung S. (Frontiers in Psychology, 2024)
Extensive research has documented the psychological, social, and academic predicament of first-generation college students. However, basic psychological mechanisms underlying the challenges experienced by these students have been understudied. Taking a cultural psychology perspective, the present research considers the role of emotional (mis)match as a key mechanism for explaining first-generation students’ lowered well-being. A sample of 344 American undergraduate students completed a survey designed to measure two aspects of emotional processing: (1) Emotional Accuracy – how accurately students perceive emotional reactions of majority-culture students (continuing-generation junior and senior students who have been socialized into college culture), and (2) Emotional Similarity –how similar students’ emotions are to the emotions experienced by majority-culture students. Emotional Accuracy predicted positive outcomes, in general, but was lower among first-generation students. Unexpectedly, Emotional Similarity predicted negative student outcomes. As one of the first studies addressing basic psychological mechanisms in college adjustment, these findings underscore the importance of understanding the roles that specific emotional processes play in social adjustment.